Financial accounting - Imdieke, Leroy F.; Smith, Ralph Eugene, 1941- (New York : John Wiley & Sons, Inc., 1987)
"Financial Accounting presents a comprehensive, straightforward description of modern-day principles of financial accounting and reporting. It is a blend of the preparation and use of financial accounting information, designed for those who have not previously studied accounting. Special care has been taken to provide a realistic balance between the procedures used in accounting and the theory and concepts upon which they are based. As such, we have emphasized both the "how" and "why" aspects of accounting. The primary objective is to describe financial accounting fundamentals as they relate to today's business environment, as we believe that this text is almost as much an introduction to business as it is to accounting. We have carefully selected the subject matter, its organization, and its description to ensure the book fits the need of all beginning business students. Consequently, the coverage is relevant for students interested in any type of business career. The book is intended for use in a one-semester or one-quarter Accounting course at the undergraduate or MBA level."
Includes index.
English text.
Keywords: Accounting